EFFECTIVENESS OF EMOTION REGULATION TRAINING ON STRESS, ANXIETY, AND DEPRESSION FOR DOCTORS IN EMERGENCY DEPARTMENT DURING PANDEMIC COVID-19 - Janice Valencia; Frickson Christian Sinambela (Proyeksi: Jurnal Psikologi, 2022)
The high risk of disease transmission and mortality in the Hospital Emergency Unit can cause health workers to experience stress, anxiety, and depression. Stress, anxiety, and depression are associated with emotion regulation. Poor emotion regulation, such as poor management of negative emotions, can increase stress to depression. In the emotion regulation training, there are three sessions whose material includes the introduction of emotion regulation, awareness of positive emotions, perception of negative emotions and their forms, acceptance of positive emotions, recognition and reassessment of emotions, and appropriate instruments of self-transformation. Outcomes were measured using a questionnaire on depression, anxiety, stress scale, and cognitive emotion regulation. The variables of depression and emotion regulation have a correlation coefficient of -0.142 with a significant value of 0.69. Based on this score, depression and emotion regulation have a negative and significant relationship. The relationship between the stress variable and emotion regulation has a correlation coefficient of -0.486 with a significant value of 0.154. Based on this score, depression and emotion regulation have negative and significant relations. Based on the different tests, the results of the pre-test and post-test were stress (0.005), depression (0.005), and emotion regulation (0.013). Emotion regulation training can reduce stress and depression for doctors in the Emergency Unit.